Yin and Yang: the dual effects of interferons on hematopoiesis - Demerdash, Yasmin; Kain, Bailee; Essers, Marieke; King, Katherine Y. (Experimental hematology, 2021)
Interferons are an ancient and well-conserved group of inflammatory cytokines most famous for their role in viral immunity. A decade ago, we discovered that interferons also play an important role in the biology of hematopoietic stem cells (HSCs), which are responsible for lifelong blood production. Though we have learned a great deal about the role of interferons on HSC quiescence, differentiation, and self-renewal, there remains some controversy regarding how interferons impact these stem cells, with differing conclusions depending on experimental models and clinical context. Here, we review the contradictory roles of Type 1 and 2 interferons in hematopoiesis. Specifically, we highlight the roles of interferons in embryonic and adult hematopoiesis, along with short-term and long-term adaptive and maladaptive responses to inflammation. We discuss experimental challenges in the study of these powerful yet short-lived cytokines and strategies to address those challenges. We further review the contribution by interferons to disease states including bone marrow failure and aplastic anemia as well as their therapeutic use to treat myeloproliferative neoplasms and viral infections, including SARS-CoV2. Understanding the opposing effects of interferons on hematopoiesis will elucidate immune responses and bone marrow failure syndromes, and future therapeutic approaches for patients undergoing HSC transplantation or fighting infectious diseases and cancer.
Gesehen am 21.05.2021